1989
DOI: 10.1164/ajrccm/140.4.1028
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan (Hyaluronic Acid) in Bronchoalveolar Lavage Fluid during the Development of Bleomycin-induced Alveolitis in the Rat

Abstract: Hyaluronan (hyaluronate or hyaluronic acid) was measured in bronchoalveolar lavage (BAL) fluid from rats during a 30-day period after a single intratracheal dose of bleomycin. An increase of hyaluronan (HA) in BAL fluid was apparent by 3 days after bleomycin administration. Peak HA values were reached on Day 5 and were about 75 times higher than in control animals. Analyses of urea in BAL and HA in serum indicated that the increased levels of HA in BAL, postbleomycin, could not be explained by plasma leakage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 12 publications
6
32
1
Order By: Relevance
“…Inflammatory injuries in the lung have also been shown to lead to an increase in hyaluronan in the BAL fluid (48,49). Savani et al (50) suggested that lung injury results in an increase in hyaluronan that, at least in part, mediates the inflammatory response to the injury.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory injuries in the lung have also been shown to lead to an increase in hyaluronan in the BAL fluid (48,49). Savani et al (50) suggested that lung injury results in an increase in hyaluronan that, at least in part, mediates the inflammatory response to the injury.…”
Section: Discussionmentioning
confidence: 99%
“…Studies utilizing HAS gene knock-out mice reveal that only HAS2 is required for viability with HAS2 deletion resulting in lethal abnormalities in cardiac development, which is rescued by addition of exogenous HA (9,10). Proinflammatory cytokines (TNF␣, IL-1␤) and LPS induce HA production in EC in vitro (11) and increased HA levels are observed in bronchoalveolar lavage fluid (BALF) from patients with inflammatory lung disorders such as pulmonary fibrosis, acute lung injury, and chronic obstructive pulmonary disease (12)(13)(14)(15). Further, intratracheal administration of nebulized high MW HA has been used to prevent injury in experimental emphysema (16).…”
Section: Endothelial Cells (Ec)mentioning
confidence: 99%
“…Multiple CD44 isoforms result from extensive, alternative exon splicing events (23,24) with the alternative splicing often occurring between exons 5 and 15 leading to a tandem insertion of one or more variant exons (v1-v10, or exon 6 through exon 14) within the membrane proximal region of the extracellular domain (25,26). The variable primary amino acid sequence of different CD44 isoforms is further modified by extensive N-and O-glycosylations and glycosaminoglycan (GAG) additions (5,26).…”
Section: Endothelial Cells (Ec)mentioning
confidence: 99%
“…During the experimental induction of bleomycin-induced alveolar injury in the rat there is a considerable accumulation of high molecular HYA in the oedematous interstitial alveolar space during the alveolitis phase [22,23,24], which has been attributed to alveolar interstitial fibroblast-like cells [24]. Experimental studies have also demonstrated a link between the alveolar and interstitial accumulation of HYA and the intraalveolar oedema and oedema of the fragile alveolar structure [25].…”
Section: Pulmonary Conditionsmentioning
confidence: 99%